Pengaruh Aplikasi Tiktok Terhadap Kesetiaan dalam Perkawinan: Antara Hiburan dan Penghianatan - Lazarus Satya Priyambada; Agnes Dwi Rahayu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the effects of TikTok app use on marital fidelity, highlighting the challenges couples face in the digital age. The method used is qualitative research with a literature review approach, which aims to collect and analyze various relevant sources regarding the impact of social media, particularly TikTok, on marital relationships. The results show that the use of TikTok can reduce interaction between couples, exacerbate tensions, and neglect family responsibilities, potentially leading to relationship dissatisfaction and even divorce. TikTok, as an engaging entertainment platform, can exacerbate communication problems in marriage, increase the temptation to have an affair, and negatively affect self and spousal perceptions. In addition, the study also examined the views of the biblical teachings and Canon Law of the Catholic Church on marital fidelity, which emphasize how important it is to maintain commitment in the conjugal bond as part of the Christian vocation. Based on these results, the study provides practical recommendations for couples to maintain marital harmony, including improving open communication, setting firm boundaries in the use of social media, and strengthening relationships based on faith values. The results of this study show that with a thoughtful approach, the use of social media can help couples maintain marital harmony.